ANALISA INDEKS KEANDALAN PEMBANGKIT LISTRIK PULAU MIANGAS - Nathaniel Lumalan Bijang; Yonatan Parassa; Yohanis Sampe Rompon; Toban Tiku Pairunan; Luther J. Mappadang; Arnold Robert Rondonuwu (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
Abstract The electric power generated by the power generation unit if what is generated is less than the consumer's demand for existing electric power, it will cause the load to be released from the electrical system. This condition will cause power outages on the customer's side. Calculation of the reliability of the electric power system can be analyzed from how often the electricity goes out. The disturbance data that is recorded/recorded is then analyzed using the LOLE (Loss of Load Expectation) formula. The smaller the LOLE value, the smaller the chance the system will experience interference. Many factors cause disruption of the supply of electricity from source to load/consumer, one of which is the problem of unreliable generators. To measure the ability of generators to meet electricity needs, a benchmark or reliability index of the generating system is needed, which in this study is LOLE (Loss of Load Expectation). . LOLE is expressed in units of days/years. The LOLE standard set by PT. PLN in Indonesia is: for Java and Bali it is 1 day/year while outside Java and Bali it is 3 days/year Keys Words : Loss of Load Expectation, Reliability Index, Power Elektric System, Load, Power, Elektric